POETRY ANALYSIS IN LITERARY EDUCATION BASED ON THE STEAM APPROACH (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the application of the STEAM approach (Science, Technology, Engineering, Arts, and Mathematics) in the analysis and teaching of poetry within literary education. The integration of STEAM principles into poetry analysis aims to enhance students’ critical, creative, and analytical thinking by connecting artistic expression with scientific and technological reasoning. Through this interdisciplinary method, learners are encouraged to perceive poetry not only as an aesthetic phenomenon but also as a structured system of rhythm, logic, and emotional balance. The article discusses how digital tools, visualization technologies, and creative design tasks can be effectively used to deepen students’ understanding of poetic imagery, symbolism, and emotional tone. It also highlights the role of collaborative learning, project-based methods, and interactive experiments in developing interpretive and communicative competence among students. The research emphasizes that incorporating STEAM-based strategies into poetry teaching promotes a holistic learning experience, bridging the gap between the humanities and sciences while fostering innovation, creativity, and emotional intelligence in future educators.